Coherent Conversion Between Microwave and Optical Photons-An Overview of Physical Implementations - Lambert, Nicholas J.; Rueda, Alfredo; Sedlmeir, Florian; Schwefel, Harald G. L. (Advanced Quantum Technologies, 2020)
Quantum information technology based on solid state qubits has created much interest in converting quantum states from the microwave to the optical domain. Optical photons, unlike microwave photons, can be transmitted by fiber, making them suitable for long distance quantum communication. Moreover, the optical domain offers access to a large set of very well-developed quantum optical tools, such as highly efficient single-photon detectors and long-lived quantum memories. For a high fidelity microwave to optical transducer, efficient conversion at single photon level and low added noise is needed. Currently, the most promising approaches to build such systems are based on second-order nonlinear phenomena such as optomechanical and electro-optic interactions. Alternative approaches, although not yet as efficient, include magneto-optical coupling and schemes based on isolated quantum systems like atoms, ions, or quantum dots. Herein, the necessary theoretical foundations for the most important microwave-to-optical conversion experiments are provided, their implementations are described, and the current limitations and future prospects are discussed.
CRIS-Team WoS Importer:2020-07-31

Efficient microwave to optical photon conversion: An electro-optical realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G. L. (Optica, 2016)
Linking classical microwave electrical circuits to the optical telecommunication band is at the core of modern communication. Future quantum information networks will require coherent microwave-to-optical conversion to link electronic quantum processors and memories via low-loss optical telecommunication networks. Efficient conversion can be achieved with electro-optical modulators operating at the single microwave photon level. In the standard electro-optic modulation scheme, this is impossible because both up- and down-converted sidebands are necessarily present. Here, we demonstrate true single-sideband up- or down-conversion in a triply resonant whispering gallery mode resonator by explicitly addressing modes with asymmetric free spectral range. Compared to previous experiments, we show a 3 orders of magnitude improvement of the electro-optical conversion efficiency, reaching 0.1% photon number conversion for a 10 GHz microwave tone at 0.42 mW of optical pump power. The presented scheme is fully compatible with existing superconducting 3D circuit quantum electrodynamics technology and can be used for nonclassical state conversion and communication. Our conversion bandwidth is larger than 1 MHz and is not fundamentally limited.
CRIS-Team Scopus Importer:2021-06-29

Efficient optical up-conversion by coherent sum-frequency generation for highly sensitive terahertz detection - Sedlmeir, Florian; Schwefel, Harald; Strekalov, Dmitry V.; Bauerschmidt, Sebastian; Preu, Sascha; Malzer, Stefan; Döhler, Gottfried; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Detection of weak THz signals is very challenging due to the extremely low energy of one THz photon (temperature equivalent of 48K). Frequency up-conversion to the near infra-red (NIR) and subsequent detection of the up-converted photon with sensitive, low-noise detectors is one way to achieve this task, albeit suffering form extremely poor conversion rates. Whispering gallery mode resonators (WGMRs), however, support well confined modes with high quality factors (Q) and extremely high field intensities inside the resonator, thus allowing efficient non-linear conversion rates. © 2011 IEEE.

Efficient single sideband microwave to optical conversion using a LiNbO3 WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dimitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We present a coherent microwave to telecom signal converter based on the electro-optical effect using a crystalline WGM-resonator coupled to a 3D microwave cavity, achieving high photon conversion efficiency of 0.1% with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Interfacing transitions of different alkali atoms and telecom bands using one narrowband photon pair source - Schunk, Gerhard; Vogl, Ulrich; Strekalov, Dmitry V.; Förtsch, Michael; Sedlmeir, Florian; Schwefel, Harald; Göbelt, Manuela; Christiansen, Silke; Leuchs, Gerd; Marquardt, Christoph (Optica, 2015)
Quantum information technology strongly relies on the coupling of optical photons with narrowband quantum systems, such as quantum dots, color centers, and atomic systems. This coupling requires matching the optical wavelength and bandwidth to the desired system, which presents a considerable problem for most available sources of quantum light. Here we demonstrate the coupling of alkali dipole transitions with a tunable source of photon pairs. Our source is based on spontaneous parametric downconversion in a triply resonant whispering gallery mode resonator. For this, we have developed novel wavelength-tuning mechanisms that allow a coarse tuning to either the cesium or rubidium wavelength, with subsequent continuous fine-tuning to the desired transition. As a demonstration of the functionality of the source, we performed a heralded single-photon measurement of the atomic decay. We present a major advance in controlling the spontaneous downconversion process, which makes our bright source of heralded single photons now compatible with a plethora of narrowband resonant system
Keywords: Atomic; Quantum communications; Quantum optics; Spectroscopy

Maximization of the optical intra-cavity power of whispering-gallery mode resonators via coupling prism - Santamaría-Botello, G.A.; Garcia Munoz, Luis Enrique; Sedlmeir, Florian; Preu, Sascha; Preu, Sascha; Segovia-Vargas, Daniel; Atia Abdalmalak, K.; Llorente Romano, S.; García Lampérez, A.; Malzer, Stefan; Döhler, Gottfried; Schwefel, Harald; et al. (Optics Express, 2016)
In this paper, a detailed description of the optical coupling into a Whispering Gallery Mode (WGM) resonator through a prism via frustrated total internal reflection (FTIR) is presented. The problem is modeled as three media with planar interfaces and closed expressions for FTIR are given. Then, the curvature of the resonator is taken into account and the mode overlap is theoretically studied. A new analytical expression giving the optimal geometry of a disc-shaped or ring-shaped resonator for maximizing the intra-cavity circulating power is presented. Such expression takes into consideration the spatial distribution of the WGM at the surface of the resonator, thus being more accurate than the currently used expressions. It also takes into account the geometry of the prism. It is shown an improvement in the geometry values used with the current expressions of about 30%. The reason why the pump laser signal can be seen in experiments under critical coupling is explained on this basis. Then, the conditions required for exciting the highest possible optical power inside the resonator are obtained. The aim is to achieve a highly-efficient up-conversion of a THz signal into the optical domain via the second-order nonlinearity of the resonator material. (C) 2016 Optical Society of America

Nonlinear power dependence of the spectral properties of an optical parametric oscillator below threshold in the quantum regime - Shafiee, Golnoush; Strekalov, Dmitry; Otterpohl, Alexander; Sedlmeir, Florian; Schunk, Gerhard; Vogl, Ulrich; Schwefel, Harald G. L.; Leuchs, Gerd; Marquardt, Christoph (New Journal of Physics, 2020)
Photon pairs and heralded single photons, obtained from cavity-assisted parametric down conversion (PDC), play an important role in quantum communications and technology. This motivated a thorough study of the spectral and temporal properties of parametric light, both above the optical parametric oscillator (OPO) threshold, where the semiclassical approach is justified, and deeply below it, where the linear cavity approximation is applicable. The pursuit of a higher two-photon emission rate leads into an interesting intermediate regime, between above OPO threshold and very low pump power, where the OPO still operates considerably below the threshold but the nonlinear cavity phenomena cannot be neglected anymore. Here, we investigate this intermediate regime and show that the spectral and temporal properties of the photon pairs, as well as their emission rate, may significantly differ from the widely accepted linear model. The observed phenomena include frequency pulling and broadening in the temporal correlation for the down-converted optical fields. These factors need to be taken into account when devising practical applications of the high-rate cavity-assisted spontaneous PDC sources.
CRIS-Team WoS Importer:2020-08-21

Nonlinear single sideband microwave to optical conversion using an electro-optic WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2016)
Nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band is achieved within a crystalline whispering gallery mode resonator, reaching 0.1% photon number conversion efficiency with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Quantum Limits of Coherent Beam Combining - Leuchs, Gerd; Müller, Christian; Sedlmeir, Florian; Chatterjee, Sourav; Haarlammert, Nicoletta; Jauregui, Cesar; Schreiber, Thomas; Limpert, Jens; Tunnermann, Andreas; Marquardt, Christoph (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
Coherent beam combining refers to the process of generating a bright output beam by merging independent input beams with locked relative phases. We report the first quantum mechanical noise limit calculations for coherent beam combining and compare our results to quantum-limited amplification. We highlight a favourable noise scaling for both pure and noisy input states.
CRIS-Team Scopus Importer:2019-05-21

Resonant electro-optic frequency comb - Rueda, Alfredo; Sedlmeir, Florian; Kumari, Madhuri; Leuchs, Gerd; Schwefel, Harald G. L. (Nature, 2019)
High-speed optical telecommunication is enabled by wavelength-division multiplexing, whereby hundreds of individually stabilized lasers encode information within a single-mode optical fibre. Higher bandwidths require higher total optical power, but the power sent into the fibre is limited by optical nonlinearities within the fibre, and energy consumption by the light sources starts to become a substantial cost factor 1 . Optical frequency combs have been suggested to remedy this problem by generating numerous discrete, equidistant laser lines within a monolithic device; however, at present their stability and coherence allow them to operate only within small parameter ranges 2–4 . Here we show that a broadband frequency comb realized through the electro-optic effect within a high-quality whispering-gallery-mode resonator can operate at low microwave and optical powers. Unlike the usual third-order Kerr nonlinear optical frequency combs, our combs rely on the second-order nonlinear effect, which is much more efficient. Our result uses a fixed microwave signal that is mixed with an optical-pump signal to generate a coherent frequency comb with a precisely determined carrier separation. The resonant enhancement enables us to work with microwave powers that are three orders of magnitude lower than those in commercially available devices. We emphasize the practical relevance of our results to high rates of data communication. To circumvent the limitations imposed by nonlinear effects in optical communication fibres, one has to solve two problems: to provide a compact and fully integrated, yet high-quality and coherent, frequency comb generator; and to calculate nonlinear signal propagation in real time 5 . We report a solution to the first problem.
CRIS-Team Scopus Importer:2019-05-02

Single sideband microwave to optical photon conversion-an electro-optic realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2017)
We present results on nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band with more than 0.1% photon number conversion efficiency with MHz bandwidth, in a crystalline whispering gallery mode resonator.
CRIS-Team Scopus Importer:2021-06-29